2018
DOI: 10.1016/j.cell.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolite-Triggered Tuft Cell-ILC2 Circuit Drives Small Intestinal Remodeling

Abstract: SUMMARY The small intestinal tuft cell-ILC2 circuit mediates epithelial responses to intestinal helminths and protists by tuft cell chemosensory-like sensing and IL-25-mediated activation of lamina propria ILC2s. Small intestine ILC2s constitutively express the IL-25 receptor, which is negatively regulated by A20 (Tnfaip3). A20-deficiency in ILC2s spontaneously triggers the circuit, and, unexpectedly, promotes adaptive small intestinal lengthening and remodeling. Circuit activation occurs upon weaning, and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
390
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(444 citation statements)
references
References 54 publications
21
390
2
3
Order By: Relevance
“…In the small intestine they have been described to produce interleukin (IL)-25 upon helminth infection. Recent reports found that the tuft cell-ILC2 circuit could be induced by microbial-derived succinate binding to G-protein coupled receptor 91 (GPR91, also known as succinate receptor 1, SUCNR1) [97][98][99][100]. Recent reports found that the tuft cell-ILC2 circuit could be induced by microbial-derived succinate binding to G-protein coupled receptor 91 (GPR91, also known as succinate receptor 1, SUCNR1) [97][98][99][100].…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In the small intestine they have been described to produce interleukin (IL)-25 upon helminth infection. Recent reports found that the tuft cell-ILC2 circuit could be induced by microbial-derived succinate binding to G-protein coupled receptor 91 (GPR91, also known as succinate receptor 1, SUCNR1) [97][98][99][100]. Recent reports found that the tuft cell-ILC2 circuit could be induced by microbial-derived succinate binding to G-protein coupled receptor 91 (GPR91, also known as succinate receptor 1, SUCNR1) [97][98][99][100].…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 99%
“…This initiates IL-13 production by ILC2s, which feeds back on epithelial progenitor cells and biases their differentiation into goblet and tuft cells, thus promoting a positive feed-forward loop that promotes worm clearance [93][94][95]. In the context of helminth infection, however, SUCNR1 signalling appeared redundant or absent, although downstream activation of Trpm5 and IL-25 occurs [99,100], although one of these studies showed that activation of this type 2 circuit by Tritrichomonas-derived succinate protected from subsequent infection with helminths [97]. SUCNR1 is specifically expressed on small intestinal tuft cells, and ligation with succinate induces a downstream chemosensing pathway involving α-gustducin (Gnat3) and Trpm5.…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 99%
“…In addition, receptor activator of nuclear factor κB ligand (RANKL) expressed by CCR6 + ILC3s negatively regulate ILC3 abundance and activity through interaction with its receptor RANK on adjacent ILC3s . Besides these inhibitory receptors, signaling molecules such as Ikaros, A20, and microRNA miR17~92 have also been shown to control ILC3 and ILC2 homeostasis and effector functions under various conditions . Beyond these intrinsic control mechanisms, regulatory T cells extrinsically inhibit innate lymphocytes activation by various mechanisms.…”
Section: Distinctive Not Shared Cytokine Production By Gut Ilc3 Andmentioning
confidence: 99%
“…In addition to mechanosensing, a recent study demonstrated that several metabolites from a consortium of commensal spore‐forming bacteria (predominantly Clostridial species) promote 5‐HT biosynthesis by colonic enterochromaffin cells in colonized mice . In response to microbes, IECs also secrete a number of cytokines and effector molecules including interleukin‐25 (IL‐25) and SAA . These effectors regulate the development and function of intestinal immune cells, as described in the next section of this review.…”
Section: Microbiota–iec Crosstalkmentioning
confidence: 99%
“…37 In response to microbes, IECs also secrete a number of cytokines and effector molecules including interleukin-25 (IL-25) and SAA. 38,39 These effectors regulate the development and function of intestinal immune cells, as described in the next section of this review. Collectively, these recent findings indicate that a broad range of IEC functions are affected by sensing of intestinal microbes (Table 1); however, it is worth noting that many of these studies were performed in the context of pathogenic microbial infection.…”
Section: Microbial Regulation Of Iec Growth and Functionmentioning
confidence: 99%